Performance improvement of ohmic contacts on Al-rich n-AlGaN grown on single crystal AlN substrate using reactive ion etching surface treatment. (6th June 2017) - Sarkar, Biplab; Haidet, Brian B.; Reddy, Pramod; Kirste, Ronny; Collazo, Ramon; Sitar, Zlatko
Abstract: Four orders of magnitude improvement in specific contact resistivity of Al-rich n-AlGaN grown on single crystal AlN substrates is achieved by surface treatment based on reactive ion etching (RIE). The ohmic contacts to as-grown Al-rich n-AlGaN/AlN exhibit a high contact resistance and nonlinearity due to a large Schottky barrier and low dislocation density. The RIE surface treatment reduces the barrier height at the free surface by ∼0.5 eV and is also expected to introduce a defective surface required for ohmic contact formation.